2022
DOI: 10.17219/dmp/149342
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the risk of COVID-19 transmission through aerosol-generating procedures

Abstract: Background. The outbreak of the coronavirus disease 2019 (COVID-19) pandemic was associated with the provision of multiple guidelines for the dental profession. All elective procedures were restricted, and only emergency procedures were performed. There was fear and anxiety among dentists while performing aerosol-generating procedures (AGPs), as they were considered to pose a high risk of COVID-19 transmission.Objectives. The aim of this study was to assess the risk of infection with severe acute respiratory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…23 Although an initial report highlighted the risk of Sars-Cov-2 transmission in dental settings, 5 recent studies have reported that the actual risk of Sars-Cov-2transmission is considerably low. 24,25 There may have been no scientific reason for patients to refrain from necessary dental attendance because of COVID-19. The government and dental associations need to provide patients with up-to-date and relevant evidence-based information on dental attendance during the pandemic periods based on scientific evidence.…”
Section: Discussionmentioning
confidence: 99%
“…23 Although an initial report highlighted the risk of Sars-Cov-2 transmission in dental settings, 5 recent studies have reported that the actual risk of Sars-Cov-2transmission is considerably low. 24,25 There may have been no scientific reason for patients to refrain from necessary dental attendance because of COVID-19. The government and dental associations need to provide patients with up-to-date and relevant evidence-based information on dental attendance during the pandemic periods based on scientific evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have suggested that the aerosols generated during dental procedures do not pose a high risk compared to the non-aerosol procedure, other studies have demonstrated that aerosol reduction is significant in disease transmission during dental procedures, despite methodological limitations. 28,29 However, it is recommended that all patients be treated for potential SARS-CoV-2 infection once the infection can be asymptomatic or pre-symptomatic. 14 Therefore we recommend that dentists be careful when performing aerosol generating procedures, and avoid them whenever possible until there is further evidence on this matter.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Manzar et al concluded that all dental operations, whether they generate an aerosol or not, can disseminate the virus. 27 As a result, all safety precautions must be used equally. Most participants knew who to report to in the event of unprotected contact with a known or suspected coronavirus-positive patient, and what to do if they developed symptoms.…”
Section: Discussionmentioning
confidence: 99%